Pedagogical System of Pre-Conscription Youth Training for Military Service - Tarakhanov Akrom Abdullakhakimovich (Periodica Journal, 2022)
The most important condition for the construction of modern Armed Forces and their combat readiness is the effective and highquality preparation of pre-conscription youth for military service. The problem of training conscripts, fulfilling the personnel order of the Armed Forces, has always been in the focus of attention of researchers, but it was not a priority. Its severity was removed by the volume of the conscription contingent, which allowed for a thorough selection of candidates for military accounting specialties requiring preliminary professional training, as well as a service life sufficient for the training and upbringing of a serviceman actually «from zero».
Keywords: training; youth; efficiency; organization